Digital Health Literacy for Bachelor Program Students at Indonesia University Year 2022 - Sjamssuddin, Irfan Nafis; Anshari, Dien (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Currently, it is easier for people to access information through various devices connected to internet technology. However, this raises various new concerns, one of which is the spread of false or inaccurate information. To overcome this, a more specific literacy approach is needed, namely digital health literacy. This study aims to determine the relationship between personal determinants of digital health literacy in bachelor program students at the University Indonesia. This study uses secondary data analysis with a cross-sectional design. Data was collected through a survey conducted by a research team from the Faculty of Public Health, University Indonesia, using the eHEALS instrument about digital health literacy. The analysis uses multiple linear regression with health literacy as the dependent variable and social determinants including gender, age, science groups, and pocket money as independent variables. The results showed that the level of digital health literacy in bachelor program students was in a good category (M=3.14; SD=0.501). The results of the unadjusted model regression test show that the variables age (ß=0.205; 95% CI = 0.015-0.396) and pocket money (ß=1.011; 95% CI = 0.140-1.882) are significantly related to digital health literacy, while the results of the adjusted regression test the model shows that no variable has a confounder effect. The conclusion of this study is that age and pocket money affect the level of digital health literacy in bachelor program students at the University Indonesia. Therefore, efforts are needed to develop health education programs that can reach students from various backgrounds.